Multiphysics modelling of powder bed fusion for polymers - Tan, Pengfei (2023)
Polymeric materials for powder bed fusion additive manufacturing have been attracting extensive research interest due to their vast potential for fabricating end-use functional parts. Here, a high-fidelity multiphysics approach combining the discrete element model with the computational fluid dynamics model has been developed to simulate the printing process of polymers in powder bed fusion, involving powder recoating, melting, and coalescence. The developed approach considers particle flow dynamics, the reflection, absorption, and transmission of infrared laser radiation, and the viscous flow of polymer melt. The pore formation mechanisms due to lack of fusion and gas entrapment in polyamide 12 parts printed via selective laser sintering are studied. The simulation results reveal that lower polymer viscosity would be beneficial to the densification rate of the printed parts. Excessively small powder particles would degrade powder bed quality due to the agglomeration of polymer powder, thus leading to high porosity in the printed parts.